2012
DOI: 10.2166/wh.2012.067
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic effect of Escherichia coli inactivation by sequential disinfection with low level chlorine dioxide followed by free chlorine

Abstract: To the best of our knowledge, there was little information available on pathogen removal using low level disinfectant followed by free chlorine in sequential disinfection (SD). This study investigated Escherichia coli inactivation by four types of disinfection: single step disinfection (SSD), SD, traditional sequential disinfection (TSD) and mixed disinfectant disinfection (MDD). Results indicated that SD had higher ability to inactivate E. coli than the others, indicating there was a positive synergistic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
2
6
0
1
Order By: Relevance
“…However, chlorine dioxide has the strongest inactivation effect at pH 8.7, which is consistent with the trends of chlorine dioxide inactivation of Pseudomonas aeruginosa and Staphylococcus aureus in water [17]. In other scenarios, the higher k value of Escherichia coli inactivation by sequential disinfection with a low level chlorine dioxide followed by free chlorine was obtained at lower pH [18].…”
Section: Effect Of Ph and Temperature On N Europaea Disinfection Kineticssupporting
confidence: 83%
“…However, chlorine dioxide has the strongest inactivation effect at pH 8.7, which is consistent with the trends of chlorine dioxide inactivation of Pseudomonas aeruginosa and Staphylococcus aureus in water [17]. In other scenarios, the higher k value of Escherichia coli inactivation by sequential disinfection with a low level chlorine dioxide followed by free chlorine was obtained at lower pH [18].…”
Section: Effect Of Ph and Temperature On N Europaea Disinfection Kineticssupporting
confidence: 83%
“…In this context, many authors have reported the formation of chlorate and perchlorate by CDA electrolyses in aqueous solutions containing chlorides [38][39][40]. ClO -+ H2O2 → Cl -+ 3 /2O2 + 2H + + 2e - [10] 2H + + 2ClO3 -+ H2O2 → 2ClO2 + 2H2O + O2 [11] This latter reaction leads to the formation of chlorine dioxide, an excellent disinfectant with no tendency to form disinfection by-products, and may take place preferentially near the anode surface due to the local acidic pH formed by the water oxidation reaction [Eq.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, many water disinfection technologies have been developed within the last years [6][7][8]. In this sense, several authors have reported the elimination of microorganisms, mainly E. coli, by the addition of chemical reagents such as ozone, hydrogen peroxide or chlorine derivate products [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The mode of action of C102 on E. coli was assessed, and the observations of the efflux of potassium strongly implicate the loss of permeability control as the primary lethal event at the physiological level, with nonspecific oxidative damage to the outer membrane leading to the destruction of the transmembrane ionic gradient (4). The o-nitrophenyl-(3-Dgalactoside assay suggested that the permeability of cell wall rather than the viability of E. coli were changed under 0.02 mg/liter C102 treatment and the coexistence of residual C102 and free chlorine also plays an active synergistic effect (41). Both the 500-and 1,000-ppm levels of C102 gas for the 24-h treatment were successful in rendering all the conidia of hyphomycete organisms Cladosporium cladosporioides, Penicillium chrysogenum, and Stachybotrys chartarum completely nonculturable (39).…”
Section: Resultsmentioning
confidence: 99%